Night of the puppet people - Stine, R. L. (New York : Scholastic Inc., 2015)
Ben and Jenny Renfro are terrified of puppets and they don't know why. The twins are determined to defeat their class rivals by winning their school's talent contest. And that means doing whatever it takes. Even if they have to surround themselves by the thing they hate most--puppets!
4.2
3-6
470L
Keywords: Puppets -- Fiction; Talent shows -- Fiction; Puppets -- Fiction; Talent shows -- Fiction; Horror fiction